Composition dependence of oxidation resistance in high entropy ultra-high temperature ceramics - Lavina Backman; Joshua Gild; Mingde Qin; Jian Luo; Elizabeth J. Opila (Open Ceramics, 2024)
High entropy ultra-high temperature ceramics (HE-UHTCs) have garnered intense research interest due to the potential for optimized oxidation and mechanical properties for extreme environment applications. HE-UHTCs are expected to oxidize according to the thermodynamic favorability of their respective oxidation reactions, which varies according to the periodic grouping. Based on this, the oxidation resistance of equimolar (metals-basis) group IV + V (HfZrTiTaNb), group IV + V + VI (HfZrTiTaMo) and group IV + VI (HfZrTiMoW) carbides and borides were evaluated at 1700°C in 1 mol% O2 for 5 min and compared. Group IV elements oxidized preferentially in all three compositions. Group V element-containing carbides exhibited the lowest oxidation resistance, attributed to the formation of intergranular liquid oxides. (HfZrTiMoW)C exhibited the best resistance among the carbides. The diborides exhibited similar material consumption, reinforcing the hypothesis that the oxidation behavior under these conditions is controlled by the presence of boria. These findings provide direction for HE-UHTC composition design for oxidation resistance.